Microwave magnetoelectric effect in magnetostatic ferrite resonators: role of surface electrode configurations - Kamenetskii, E.O.; Saha, A.K.; Awai, I. (IEEE transactions on magnetics, 2000)
The possibility of realizing artificial bianisotropic media with local properties is a very topical subject. Such materials will exhibit properties unknown for natural materials and should open a way to a new generation of microwave devices. In recent theoretical and experimental investigations it has been shown that magnetostatic-wave ferrite resonators with special-form surface metallic electrodes can be considered as structural elements for artificial bianisotropic materials. New experimental investigations and calculations of these particles is on the agenda. In this paper the role of surface electrode configuration is considered. The results show a strong transformation of oscillating spectra when one-dimensional surface electrodes are changed by two-dimensional ones. Based on an analysis of experimental spectra, it is clear that two-dimensional surface electrodes can be used for effective magnetoelectric coupling.